Inhibition of p38 MAPK Mitigates Lung Ischemia Reperfusion Injury by Reducing Blood–Air Barrier Hyperpermeability - Wang, Tiantian; Liu, Chunxia; Pan, Ling-hui; Liu, Zhen; Li, Chang-long; Lin, Jin-yuan; He, Yi; Xiao, Jing-yuan; Wu, Siyi; Qin, Yi; Li, Zhao; Lin, Fei (Frontiers in Pharmacology, 2020)
Lung ischemia-reperfusion injury (LIRI) is a complex pathophysiological process during many clinical conditions, such as lung transplantation, acute lung injury (ALI), etc. The function of p38 Mitogen-activated protein kinase (MAPK) in LIRI is still unclear. Therefore, we investigated the function of p38 MAPK in LIRI and explored the mechanism of inhibiting p38 MAPK in pulmonary blood-air hyperpermeability both in vivo and vitro. 72 rats were divided into four groups at random: Control group, I/R (ischemia-reperfusion) group, SB203580 (p38 MAPK inhibitor) group and I/R+SB203580 group. The rat pulmonary microvascular endothelial cells (rPMVECs) were divided into five groups: control group, control shRNA group, p38 MAPK shRNA group, OGD/R group (cells subjected with non-serum and -glucose medium for 1 h, followed by reoxygenation for 4 h) and OGD/R+p38 MAPK shRNA group. Degree of lung injury was assessed by HE staining, TEM and inflammatory response. Pulmonary blood-air barrier permeability was evaluated by evans blue, W/D ratios and total proteins in BALF. Protein expression of AQP1, ICAM-1, ZO-1 and VE-cadherin were estimated by western blot and Immunohistochemistry in vivo and vitro I/R model. Lung I/R induced lung injury and high permeability of blood-air barrier while pretreatment with SB203580 decreased lung injury and reduced the high permeability of blood-air barrier in rat models. In vitro rPMVECs model, OGD/R promoted hyperpermeability of endothelial barrier. However, inhibition of p38 MAPK attenuated OGD/R-induced cell injury and thus maintained endothelial barrier integrity. Summarily, our results proved that inhibition of p38 MAPK alleviates LIRI through decreasing pulmonary inflammation and blood-air hyperpermeability.